Microstructure and ferroelectric properties of bi-excess Bi4Ti3O12 thin films grown on Si and Pt/Ti/SiO2/Si substrates. (2nd January 2020) - Liu, Yong; Fan, Liqun; Yi, Wentao; Yan, Chunyan; Ma, Jie; Ji, Qiyan; Lin, Qiaoli
Abstract: Bismuth layer-structured ferroelectric Bi4 Ti3 O12 thin films have been deposited on n -type Si(111) and Pt(111)/Ti/SiO2 /Si substrates using rf-magnetron sputtering process. The effects of substrates and annealing treatments on microstructure and ferroelectric properties were investigated. Scanning electron microscopy and X-ray diffraction patterns exhibited that the as-deposited thin films were noncystalline and transformed to crystalline Bi4 Ti3 O12 phase with a second phase of Bi12 TiO20 after annealed at 700 °C. Ferroelectric properties showed that as-deposited thin film in metal-ferroelectric-semiconductor capacitor form and annealed thin film in metal-ferroelectric-metal form exhibited typical ferroelectric behaviors, wherein the values of remnant polarization were around 0.8 µC/cm 2 and 4.8 µC/cm 2, respectively.